Hubungan Kualitas Pelayanan, Kepuasan Dan Kepercayaan Pasien Poli Umum Terhadap Loyalitas Di Puskesmas Ciomas Bogor Tahun 2024: Association Between Service Quality, Satisfaction, and Patient Trust with Loyalty at Ciomas Public Health Center, Bogor, 2024 - Yaya, Nurmalia; Mohamad Yaser; Cici Demiyati (Journal of Public Health Education, 2025)
Introduction: Loyal pati ents are those who consistently choose and use healthcare services from one particular place or healthcare provider. Based on data from WHO in Indonesia itself, it is still found that patient loyalty is low in the sense of less than 80%. Objectives: The purpose of this study was to determine the relationship between service quality, satisfaction and trust of general polyclinic patients towards loyalty at the Ciomas Bogor Health Center in 2024. Method: The research method is quantitative with a cross sectional approach. The s ampling technique in this study uses accidental sampling of 100 respondents who are targeted. Data analysis was carried out univariate and bivariate with chi square test. Result: Based on the results of the study, it is known that there is a significant relationship between service quality and general poly patient loyalty as a result of the chi-square test (p=0.001< 0.05). There was a relationship between patient trust and loyalty of chi-square test results (p = 0.002 < 0.05). Conclution: This research it can be concluded that there is a relationship between service quality, satisfaction and trust of general poly patients towards loyalty at the Ciomas Bogor Health Center in 2024.